Effects of Acceleration on Ground Reaction Forces Collected in Healthy Dogs at a Trot - Budsberg, S. C.; Rytz, U.; Johnston, S. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
The aim of this study was to assess, whether or not, visual grading of changes in subject acceleration during force plate collection within a fixed, measured velocity range was adequate to control acceleration/deceleration. A second question was, whether or not, visual grading of the trials was adequate to prevent significant changes in ground reaction forces within a controlled velocity range. Eight healthy, non-chondrodysplastic dogs, of varying breeds, were used in the study. Each dog was tested in four different protocols. The order in which the dogs completed the different protocols was determined randomly. During all of the protocols, the dogs trotted across the measured testing area within a velocity range of 1.6 to 1.9 m/s. The protocols varied in the amount of acceleration or deceleration allowed in the testing area and the methods of evaluating the acceleration or deceleration. Significant differences in ground reaction force measurements were found, with variations in the acceleration and deceleration. The majority of changes were found in the craniocaudal axis during acceleration and deceleration. Vertical axis measurements were only altered in the rear limbs. Significant differences were not found in any measurement (except the stance phase duration in the rear limb) between the mechanically controlled minimal acceleration/deceleration variation protocol and the visually controlled acceleration/deceleration variation protocol. While visual observation was unable to consistently differentiate acceleration, or deceleration, changes through the testing area, it was able to eliminate enough variation in ground reaction force measurements so that differences were not found between the mechanically controlled minimal acceleration/ deceleration variation protocol nor the visually controlled acceleration/deceleration variation protocol. These results suggest that either method of collection may be acceptable for data collection depending upon the type of study being performed.The effects of acceleration variation were examined in dogs undergoing force plate gait analysis. Significant differences in ground reaction force measurements were found, with variations in the acceleration and deceleration. The majority of changes were found in the craniocaudal axis, during acceleration and deceleration. Visual observation was unable to consistently differentiate variations in acceleration through the testing area.
Keywords: Gait analysis; ground reaction forces; acceleration